Study of the Principles and Models in Web Performance Optimization - Wang Xin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the development of Web, the optimized question is becoming more and more prominent, so the Web performance optimization is inevitable. The important principle of Web Performance Optimization is understanding, and recognizing that gain must lose, the repayment is decreasing progressively, and return is diminishing at the same time, the optimized goal is the overall performance, and start from the highest level to optimize will obtain the biggest. Models of improving Web performance are as follows: sharing costs, high-speed caching, parallel processing, profiles, and using known information. To optimize the performance of Web database is also critical, such as to analyze and research from the cache, statements, tables, connection pooling, query, index, and several other aspects. Based on this study, given the crucial Web performance optimization recommendations, which will improve the performance of Web usage, accelerate the efficient use of Internet has an important significance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4660